Polymorphism of bovine STAT5A gene and its association with milk production traits in crossbred cattle of Kerala, India - Valsalan, Jamuna; Sadan, Tina; ANILKUMAR, KULANGARA; ARAVINDAKSHAN, T V (The Indian Journal of Animal Sciences, 2022)
Signal transducer and activator of transcription 5A (STAT5A) is a transcription factor that mediates signals from prolactin and growth hormone, the corresponding main regulators of lactation and growth of mammals. STAT5A is suggested to be candidate marker gene for quantitative traits in dairy cattle with respect to milk production traits. The objectives of present study were to investigate polymorphism of bovine STAT5A gene and its probable association with milk yield and milk-constituent traits in crossbred cattle. Crossbred cattle (250) in different farms of Kerala Veterinary and Animal Sciences University and different field centres of ICAR-Field progeny testing scheme, Thrissur were screened for polymorphism in exon-8 region of STAT5A gene using PCR-single-strand conformation polymorphism analysis. A synonymous polymorphism (C/T) was found at position 1071 in exon 8. All three possible genotypes were identified with estimated frequencies of 0.584 (CC), 0.332 (CT) and 0.084 (TT); the estimated allele frequencies were 0.75 (C) and 0.25 (T). The C/T genotypes demonstrated significant impact on milk fat per cent being significantly higher in CC genotype cattle in comparison to other genotypes. It is evident by this investigation that STAT5A polymorphism could be a promising indirect marker to improve milk production in crossbred cattle of Kerala.